Primary cyclical menouria: a rare presentation - Padore, Ishaan Sachin; Tambe, Sanjaykumar G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Congenital vesicouterine fistula is a rare condition usually seen in association with malformations of the genitourinary tract. We report the case of a 42 yar old nulligravida with complaints of cyclical passage of blood in the urine (menouria) with severe dymenorrhoea. Physical examination revealed well developed breasts and pubic hair with a normal patent vagina but no communication between the vagina and uterus. Cystoscopy revealed the presence of a fistulous tract in the supraishtmic part between the uterus and the bladder. A hysterectomy and uterovesical fistulectomy repair were done which offered symptomatic relief to patient.